Fiber-optic speckle interferometry for unobtrusive heartbeat monitoring - Podbreznik, Peter (LAHA (Online ed.), 2013)
In this paper, a speckle interferometer with optical fiber system is reported for unobtrusive heartbeat monitoring. The sensor consists of a laser diode butt-coupled to the plastic optical fiber whose exit face projects speckle patterns onto a linear optical sensor array. Speckle images are acquired in a sequence and 1D features are extracted based on time differentiation and space averaging. These were analyzed in the frequency band that corresponds to the cardiac activity in order to detect individual heartbeats. Preliminary experiments with five young, healthy persons lying supine on a mattress with embedded optical fiber showed the proposed system and detection algorithms are highly efficient.
Keywords: band-pass filtering; fiber-optic speckle interferometry; heartbeat detection; human vital signs; speckle interferometry; unobtrusive monitoring